The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1111/j.1365-2923.1988.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the psychiatric skills of the general practice trainee: an evaluation of a group training course

Abstract: Fourteen general practice trainees took part in a course specifically designed to improve their psychiatric interviewing skills. The trainees were instructed in the problem-based model and were taught in a group setting with the use of videotape feedback. A significant improvement was demonstrated in the trainees' ability to identify psychiatric illness accurately, and there were significant changes in their interview behaviours after training. Those who were below average before training showed the greatest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
93
0
7

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(107 citation statements)
references
References 14 publications
1
93
0
7
Order By: Relevance
“…O grupo de pesquisadores dessa Instituição, coordenado pela professora Linda Gask, trabalha em conjunto com o Instituto de Psiquiatria de Londres e possui vasta experiência na condução, bem como na avaliação, de cursos de saúde mental direcionados para profissionais da atenção primária 20,21,22,23 . Na oficina oferecida para médicos de família, que ocorre duas vezes por ano, com aulas semanais de um ou dois turnos por um período de 8 semanas, defende-se o emprego de múltiplas técnicas de aprendizagem 24 :…”
Section: Discussão Estratégias Educativas Dirigidas Para Os Profissiounclassified
“…O grupo de pesquisadores dessa Instituição, coordenado pela professora Linda Gask, trabalha em conjunto com o Instituto de Psiquiatria de Londres e possui vasta experiência na condução, bem como na avaliação, de cursos de saúde mental direcionados para profissionais da atenção primária 20,21,22,23 . Na oficina oferecida para médicos de família, que ocorre duas vezes por ano, com aulas semanais de um ou dois turnos por um período de 8 semanas, defende-se o emprego de múltiplas técnicas de aprendizagem 24 :…”
Section: Discussão Estratégias Educativas Dirigidas Para Os Profissiounclassified
“…In a study of medical students, he has shown that audio/videotaped observation of interviews with feedback is superior to traditional methods (Maguire et al, 1978). Cask et al (1988) demon strated that use of group video feedback training was effective in improving psychiatric skills in a group of general practitioners. Rutter & Cox (1981) pub lished a series of studies examining the effects of in terview style on the quality of factual information obtained and the emotional response elicited.…”
mentioning
confidence: 98%
“…un tema di ricerca molto diffuso, producendo ogni anno, un incremento esponenziale di pubblicazioni che prendono in considerazione diversi aspetti, quali ad esempio l'efficacia del modello teorico (Smith & Hope, 1991;Smith, 1996;Zimmermann, 1996), la validazione di sistemi di classificazione dell'intervista (Brown et al, 1995;Cape, 1996;Roter, 1977;1993;Ong et al, 1995;Stiles, 1978) o di corsi formativi nell'uso di tecniche comunicative (Goldberg et al, 1980;Gask et al, 1987;1988;Smiths al, 1998).…”
unclassified